Transcriptome and metabolome analyses revealed the response mechanism of pepper roots to Phytophthora capsici infection - Lei, Gang; Zhou, Kun-Hua; Chen, Xue-Jun; Huang, Yue-Qin; Yuan, Xin-Jie; Li, Ge-Ge; Xie, Yuan-Yuan; Fang, Rong (BMC genomics, 2023)
Background Phytophthora root rot caused by the oomycete Phytophthora capsici is the most devastating disease in pepper production worldwide, and current management strategies have not been effective in preventing this disease. Therefore, the use of resistant varieties was regarded as an important part of disease management of P. capsici . However, our knowledge of the molecular mechanisms underlying the defense response of pepper roots to P . capsici infection is limited. Methods A comprehensive transcriptome and metabolome approaches were used to dissect the molecular response of pepper to P . capsici infection in the resistant genotype A204 and the susceptible genotype A198 at 0, 24 and 48 hours post-inoculation (hpi). Results More genes and metabolites were induced at 24 hpi in A204 than A198, suggesting the prompt activation of defense responses in the resistant genotype, which can attribute two proteases, subtilisin-like protease and xylem cysteine proteinase 1, involved in pathogen recognition and signal transduction in A204. Further analysis indicated that the resistant genotype responded to P . capsici with fine regulation by the Ca 2+ - and salicylic acid-mediated signaling pathways, and then activation of downstream defense responses, including cell wall reinforcement and defense-related genes expression and metabolites accumulation. Among them, differentially expressed genes and differentially accumulated metabolites involved in the flavonoid biosynthesis pathways were uniquely activated in the resistant genotype A204 at 24 hpi, indicating a significant role of the flavonoid biosynthesis pathways in pepper resistance to P . capsici . Conclusion The candidate transcripts may provide genetic resources that may be useful in the improvement of Phytophthora root rot-resistant characters of pepper. In addition, the model proposed in this study provides new insight into the defense response against P. capsici in pepper, and enhance our current understanding of the interaction of pepper– P. capsici .